Miracle on 34th Street - Seaton, George, 1911-1979.; Perlberg, William, 1899-1969.; Davies, Valentine, 1905-1961.; O'Hara, Maureen, 1920-; Payne, John, 1912-1989.; Gwenn, Edmund, 1875-1959.; Lockhart, Gene, 1891-1957.; Wood, Natalie; Hall, Porter, 1888-1953.; Frawley, William, 1887-1966.; Cowan, Jerome, 1897-1972.; Tonge, Philip, 1897-1959.; et al. (Beverly Hills, Calif. : 20th Century Fox Home Entertainment, 2006)
The real Santa is hired by Macy's to play the department store's Santa in the Thanksgiving Day parade, but has to prove in court that he is who he says he is.
Title from container.
"Colorized" version originally released in 1985 ; Originally released, in b&w, as a motion picture in 1947.
Special features: Disc one: All-new colorized version; feature audio commentary by Maureen O'Hara ; Disc two: Original version in black & white; feature audio commentary by Maureen O'Hara; AMC Backstory: 'Miracle on 34th Street;' Fox Movietone News footage: "Hollywood spotlight;" 'Miracle on 34th Street' TV version; "Macy's Thanksgiving Day Parade: floating in history" featurette; promotional short; poster gallery.
Maureen O'Hara, John Payne, Edmund Gwenn, Gene Lockhart, Natalie Wood, Porter Hall, William Frawley, Jerome Cowan, Philip Tonge.
DVD, region 1, full screen (1.33:1) presentation; single layer (disc 1), dual layer (disc 2), NTSC.
Keywords: Macy's (Firm); Santa Claus; Department store Santas; Parades -- New York (State) -- New York; Defense (Criminal procedure); Feature films; Christmas films; Fantasy films; Romantic comedy films; Trials in motion pictures; Films for the hearing impaired; Family